Population balance model and experimental validation for reactive dissolution of particle agglomerates. (4th January 2018) - Zhao, Wenli; Jama, Mohamed Ali; Buffo, Antonio; Alopaeus, Ville
Highlights: A population balance model for dissolution of particle agglomerates is proposed. The model combines shrinkage and breakage of particles. The high-order moment conserving method of classes is adopted. Beta distribution is introduced as the breakage daughter size distribution. The solid-liquid interface concentration is estimated under physical constrains. Abstract: We propose a population balance model coupled with a mass transfer model to simulate the simultaneous shrinkage and breakage of particles during the reactive dissolution of particle agglomerates in stirred tank. The high-order moment-conserving method of classes is adopted to solve the population balance model. In the mass transfer model, the driving force is estimated by considering the physical constraints including electroneutrality, water dissociation and dissolution equilibrium. The simulation results, including the concentration and the particle size distribution of the final products, were validated by experiments carried out in a laboratory scale stirred tank. The unknown physical parameters in the particle breakage model were fitted against the experimental data. The results underline the importance of particle breakage in the reactive dissolution modeling under the investigated operating conditions. Several daughter size distributions functions found in literature were tested. Among them, the beta distribution provides the most flexible way to describe breakage of the particle agglomerates.